Planktonic foraminiferal biostratigraphy and depositional setting of the Cretaceous Parh Limestone, Quetta, western Sulaiman Fold-Thrust Belt, Balochistan, Pakistan - Muhammad, Baz; Khan, Suleman; Mohibullah, Mohibullah; Kasi, Aimal Khan; Jan, Irfan U.; Ghani, Mukhtiar (Journal of Himalayan Earth Sciences, 2018)
Parh Limestone at Hanna Lake and Murree Brewery sections, Quetta, yield a rich and diverse planktonic foraminifera comprising of forty-three species from fifteen different genera. This highly diverse assemblage is characterized by many short-range species suggesting Globotruncana ventricosa Biozone of middle-late Campanian for the Parh Limestone in the Quetta region. The Globotruncana ventricosa co-occur with the stratigraphically older taxa Dicarinella asymetrica and D. concavata, which is interpreted as an upward extension of these taxa to younger global G. ventricosa Biozone in this part of the eastern Tethys. The upward extension of D. asymetrica and D. concavata to G. ventricosa Biozone is supported by the high diversity of planktonic foraminifera characterized by the appearance of many species of Globotruncana, Heterohelix, Pseudotextularia and Ventilabrella which is a typical character of G. ventricosa Biozone recorded in other Tethyan regions, as well. The Parh Limestone was also studied for microfacies analysis to understand the depositional setting. Two microfacies, including Globotruncana-rich Mud-Wackestone microfacies (KP-1) and Globotruncana- Heterohelix Wacke-Packstone microfacies (KP-2) have been recognized. Based on these microfacies, an outer ramp to open basinal depositional setting has been assigned to the Parh Limestone in the study area.